Making land use – Transport models operational tools for planning: From a top-down to an end-user approach. (July 2016) - Saujot, Mathieu; de Lapparent, Matthieu; Arnaud, Elise; Prados, Emmanuel
Abstract: Land Use and Transport Integrated models (LUTIs) are promising approaches for urban planning. There is large literature describing their technical architectures or using them in various scientific contexts. Yet little attention has been paid to expectations of practitioners (planners) and to the operational use of such models. The gap between lab application and operational use for planning practice is still to be filled. We shed light on what would make them definitely accepted and more used by planners to evaluate a range of urban and transport policies. In addition to literature review and our own experience dealing with urban planning agencies, we have interviewed different types of end users in France to identify their motivations and barriers to use LUTI models. The results show demand for a far more bottom-up oriented approach: the models should consider objectives and general needs of end users to live up to their expectations. Only a closer collaboration between modelers and end users, and more efforts to integrate modeling into urban planning, will make LUTIs considered as relevant approaches. Highlights: A gap between theory and practice has to be filled for LUTI modeling. Efforts to make LUTI operational tools are more critical than technical improvements. Academics should build up on more bottom-up approaches. Calibration and validation procedures should be adapted to specific LUTI use.